2002
DOI: 10.1177/0306624x02461006
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Recurrent Maltreatment and Offending Behaviour

Abstract: This article considers recurrent maltreatment and offending behaviour. The sample was 60 males and 19 females (11 to 18 years) resident within a secure institution in England and considered a risk to themselves and/or others. Overall, 20.8% had not experienced maltreatment, 6.5% had experienced a single incident, 11.7% were repeat victims (same perpetrator), 6.5% were revictimised (different perpetrators), and more than half (54.5%) had suffered both repeat and revictimisation. Of those who had committed a vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…As a consequence, for these girls, any attention is sought and valued, be it positive or negative. Hamilton, Falshaw, and Browne (2002) also found a connection between recurrent abuse and serious offending behavior in an incarcerated sample. Although this sample was very small (19 women), the authors found support for the hypothesis that victimization and revictimization led to more violence.…”
Section: Studies Of Violent Womenmentioning
confidence: 76%
“…As a consequence, for these girls, any attention is sought and valued, be it positive or negative. Hamilton, Falshaw, and Browne (2002) also found a connection between recurrent abuse and serious offending behavior in an incarcerated sample. Although this sample was very small (19 women), the authors found support for the hypothesis that victimization and revictimization led to more violence.…”
Section: Studies Of Violent Womenmentioning
confidence: 76%
“…Finally, various investigators have demonstrated associations between CM and concurrent/subsequent violent behavior (e.g., [10,24,25]) but few have adequately controlled for the individual and environmental factors that may influence CM exposure and WC. One way researchers have addressed this problem is through studies where a quasiexperimental group is retrospectively selected based on CPS reports and compared with a matched control group.…”
Section: A Link Between Maltreatment and Weapon Carrying?mentioning
confidence: 99%
“…A persistent problem in developing a coherent research agenda has been the absence of consistent and valid definitions of recurrence and severity. Recurrence has been defined in terms of the duration of children and youth services (Barnett, Manly, & Cicchetti, 1993), the frequency of substantiated incidents (Lemmon, 1997(Lemmon, , 2006Smith & Thornberry, 1995), the type and number of perpetrators (Hamilton, Falshaw, & Browne, 2002), as well as a combination of duration, recurrence, and timing (Stewart, Livingston, & Dennison, 2008). Maltreatment severity measures have relied upon severity scales (Barnett et al, 1993; designed for clinical assessments of injury or danger to children but not easily adapted for research.…”
Section: The Effects Of Maltreatment Dimensions On Youth Offendingmentioning
confidence: 99%
“…Studies that have examined the effects of maltreatment recurrence (Hamilton et al, 2002;Lemmon, 2006;Smith & Thornberry, 1995;Stewart, et al, 2008;Thornberry, Ireland, & Smith, 2001;Zingraff et al, 1993) and severity (Smith & Thornberry, 1995) report mixed results. Zingraff's (1993) comparison of samples of maltreated, school-age, and low-income children featured an examination of maltreatment subtypes with recurrence as a control variable in logistic regression models.…”
Section: The Effects Of Maltreatment Dimensions On Youth Offendingmentioning
confidence: 99%